Nanocarrier-based Delivery Approaches of Mangiferin: An Updated Review on Leveraging Biopharmaceutical Characteristics of the Bioactive - Vishwakarma, Km Khushboo; Hafeez, Abdul; Usmani, Shazia Afzal; Noor, Layba; Khan, Ishma Rahela (Current Pharmaceutical Biotechnology, 2025)
In recent years, bioactive constituents from plants have been investigated as an alternative to synthetic approaches of therapeutics. Mangiferin (MGF) is a xanthone glycoside extracted from Mangifera indica and has shown numerous medicinal properties, such as antimicrobial, anti-diarrhoeal, antiviral, anti-inflammatory, antihypertensive, anti-tumours, and anti-diabetic effects. However, there are numerous challenges to its effective therapeutic usage, including its low water solubility, limited absorption, and poor bioavailability. Nano formulation approaches in recent years exhibited potential for the delivery of phytoconstituents with key benefits of high entrapment, sustained release, enhanced solubility, stability, improved pharmacokinetics, and site-specific drug delivery. Numerous techniques have been employed for the fabrication of MGF-loaded Nano formulations, and each technique has its advantages and limitations. The nanocarriers that have been employed to fabricate MGF nanoformulations for various therapeutic purposes include; polymeric nanoparticles, nanostructure, lipid carriers, polymeric micelles, Nano emulsions, microemulsion & self-microemulsifying drug delivery system, solid lipid nanoparticles, gold nanoparticles, carbon nanotubes, transfersomes, nanoliposomes, ethosomes & transethosomes, and glycethosomes. Different biopharmaceutical characteristics (size, shape, entrapment efficiency, zeta potential, in vitro drug release, ex vivo drug permeation,, and in vivo studies) of the mentioned MGF-loaded nanocarriers have been methodically discussed. Patent reports are also included to further strengthen the potential of MGF in the management of diseases.
Keywords: targeted delivery